Employing Indigenous methodologies to transform dental and medical education - Forsyth, Cathryn; Malouf, Peter; Short, Stephanie; Irving, Michelle; Tennant, Marc; Gilroy, John (The Australian Journal of Indigenous Education, 2022)
Indigenous people in Australia experience considerably more dental and medical ill-health than non-Indigenous people. Cultural competence of dental and medical teams is crucial in the delivery of services to address these health disparities. Traditionally, cultural training has been incorporated later in health education curricula, resulting in students perceiving Indigenous health to be less important, relevant or useful in their future careers. Higher education institutions struggle to incorporate Indigenous culture into curricula to improve educational outcomes for Indigenous peoples and to increase cultural competence of staff and students. This study explores how a team of Indigenous and non-Indigenous researchers navigated the cultural interface to develop an Indigenous curricula model for dental and, potentially, medical programs in Australia. A team of Indigenous and non-Indigenous oral health, dental and social science researchers, together with a Cultural Competence Curriculum Review Reference Group comprising Indigenous and non-Indigenous members, successfully navigated the cultural interface. Collaborations between the reference group and research team at each phase of this research ensured authentication and validity of the data. This study highlights the importance of employing Indigenous methodologies when conducting Indigenous research to improve dental and medical health outcomes for Indigenous peoples.